ISLAM DAN KELUARGA - Wulan Darwati; Salsabila Zahra; Abbas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The family in the Islamic perspective is not merely a biological or social bond, but a sacred institution established through lawful marriage to fulfill Allah’s commands, as stated in QS. Ar-Rum: 21 concerning sakinah, mawaddah, and rahmah. This study aims to analyze the concept of family in Islam, including its definition, objectives, functions, principles of sakinah family development, roles of family members, and strategies for realizing an Islamic family in the context of basic education. This research employed a qualitative descriptive approach through a literature review, analyzing primary sources such as the Qur’an and Hadith, as well as secondary sources including books and scientific journals related to Islamic family education. The results indicate that the Islamic family serves as the first educational institution (madrasah), responsible for instilling faith, morality, and social responsibility. The principles of tauhid, mutual consultation, balanced roles between husband, wife, and children, and continuous religious education are essential in forming a harmonious family. The study concludes that strengthening Islamic family values contributes significantly to character education and the development of a morally upright generation.